2016
DOI: 10.3390/s16060826
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Specific Losses in the Limbs of an Epstein Frame Using a Three Epstein Frame Methodology Applied to Grain Oriented Electrical Steels

Abstract: An experimental method to characterize the magnetic properties of Grain Oriented Electrical Steel in the rolling direction is proposed in this paper. It relies on the use of three 25 cm Epstein frames combined to generate three test-frames of different lengths. This enables the identification of the effective specific losses of the electrical steel when magnetization is applied along the rolling direction. As a consequence, it evidences the deviation of the loss figures obtained using the standardised Epstein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Simulation results for comparison of current for various combinations of primary and secondary turns are presented in Figure 7. The primary and the secondary turns considered for analysis are (24,8); (32,16); (81, 18). It can be observed that the primary and the secondary turns (24,8) generates the required MF of 1 T to 1.5 T with a current range from 0.8 A to 16 A.…”
Section: Comparison For Various Number Of Turnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulation results for comparison of current for various combinations of primary and secondary turns are presented in Figure 7. The primary and the secondary turns considered for analysis are (24,8); (32,16); (81, 18). It can be observed that the primary and the secondary turns (24,8) generates the required MF of 1 T to 1.5 T with a current range from 0.8 A to 16 A.…”
Section: Comparison For Various Number Of Turnsmentioning
confidence: 99%
“…An experimental method to characterize the magnetic properties of Grain Oriented Electrical Steel in the rolling direction was proposed in [16]. In [17], a stator core shape design method is proposed to improve power density of a surface-mounted permanent magnet (SPM) motor.…”
Section: Introductionmentioning
confidence: 99%
“…where A is the cross-sectional area of the sample, is obtained and the effective magnetic path length is retrieved from (1). A similar approach has been followed by the authors of [33], who used three Epstein frames. However, small deviations from uniformity of the magnetization inside the Epstein legs inevitably occur, impairing to some extent this conclusion.…”
Section: ) Epstein Framementioning
confidence: 99%
“…The latter includes high portions from the complex magnetization of the four corners of the quadratic frame of double-overlapped sample strips. Since decades, attempts are made to attain a separation by means of a so-called effective path length [3][4][5], or by specific substitution methods [6,7]. However, long experience demonstrated that it is impossible to attain accurate results from these approaches.…”
Section: Introductionmentioning
confidence: 99%